KELENGKAPAN PENGISIAN BERKAS REKAM MEDIS PELAYANAN MEDIK RAWAT JALAN DAN PATIENT SAFETY DI RSGMP UMY - Erwin Santosa; Elsye Maria Rosa; Famella Tiara Nadya (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2014)
Background: health care givers are required to make the medical record and give priority to patient safety. The problems that often arise in medical record is charging charging medical record completeness and implementation of patient safety. The purpose of this research is to know the implementation and problems in charging medical record and patient safety that is run by koass at RSGMP UMY. Method: qualitative descriptive method. The subjects of the research koass in RSGMP UMY. Medical record file the research object 2013 as much as 367 medical record. Qualitative Data using descriptive statistics and coding interviews. Results: completeness of patient identity aspects 367 (100%) name, medical record number 338 (92,1%), place/date of birth and gender of 366 (99,7%). Increase of effective communication has not been fully carried out effectively. Improving drug safety needs to be policed for the right drug, right dose, right patient, right document 66 (68.7%) and timely and precise ways of administering 64 (66,7%). Exact location of certainty, right procedure, the right of patients to the operating date and time actions 320 (99.3%), anamnesa 322 results (100%), charging odontogram 169 (91,8%), 318 (98.7%) diagnostic, treatment action plan of 321 (99,7%), supporting and physical examination (94.5 per cent) of 120 and informed consent 71 (65,1%). Reduction of risk of infection related to medical services is already quite good but not completely orderly run. Summary: the completeness of charging medical record and implementation of patient safety in RSGMP UMY due to time limitations, the knowledge operator, not a supervisor and physician supervision.